Prediction of CO2 Permeability in NH2-MIL-53(Al)/Cellulose Acetate Mixed matrix Membranes using Theoretical Models - Mubashir, Muhammad; Fong, Yeong Yin; Leng, Chew Thiam; Keong, Lau Kok (International Journal of Integrated Engineering, 2018)
Estimation of CO2 permeability of mixed matrix membranes (MMMs) using models has importance for the design of membrane separation system. In the current article, the previously reported models were used for the calculations of CO2 permeability through new type of MMMs, NH2-MIL-53(Al)/CA. It was found that modified Maxwell model demonstrated the absolute average error (AARE %) of 1.66%, which is lower than the AARE% obtained from the other theoretical models. Besides, the results also showed that AARE% of models for the prediction of CO2 permeability was in the order of modified Maxwell model < Lewis-Nielsen model < Fleski model < Bruggeman model < Pal model< modified Fleski model < Maxwell model. Therefore, it can be concluded that modified Maxwell model is more accurate compared to other theoretical models for the prediction of CO2 permeability through NH2-MIL-53(Al)/CA MMMs.